Management of adults and children undergoing CAR t-cell therapy: best practice recommendations of the European Society for Blood and Marrow Transplantation (EBMT) and the Joint Accreditation Committee of ISCT and EBMT (JACIE) - Yakoub-Agha, Ibrahim; Chabannon, Christian; Bader, Peter; Basak, Grzegorz W.; Bonig, Halvard; Ciceri, Fabio; Corbacioglu, Selim; Duarte, Rafael F.; Einsele, Hermann; Hudecek, Michael; Kersten, Marie José; Köhl, Ulrike; et al. (Haematologica, 2019)
Chimeric antigen receptor T-cells are a novel class of anti-cancer therapy in which autologous or allogeneic T-cells are engineered to express a chimeric antigen receptor targeting a membrane antigen. In Europe, Tisagenlecleucel (KymriahTM) is approved for the treatment of refractory/relapsed Acute Lymphoblastic Leukaemia in children and young adults as well as relapsed/refractory Diffuse Large B-cell Lymphoma; Axicabtagene ciloleucel (YescartaTM) is approved for the treatment of relapsed/refractory high-grade B-cell Lymphoma and Primary Mediastinal B-cell Lymphoma. Both agents are genetically engineered autologous T-cells targeting CD19. These practical recommendations, prepared under the auspices of the European Society of Blood and Marrow Transplantation, relate to patient care and supply chain management under the following headings: patient eligibility, screening laboratory tests and imaging and work-up prior to leukapheresis, how to perform leukapheresis, bridging therapy, lymphodepleting conditioning, product receipt and thawing, infusion of chimeric antigen receptor T-cells, short-term complications including cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome, antibiotic prophylaxis, medium-term complications including cytopenias and B-cell aplasia, nursing and psychological patient support, long-term follow-up, post-authorisation safety surveillance, and regulatory issues. These recommendations are not prescriptive and are intended as guidance in the use of this novel therapeutic class.

Adenovirus infections after allogeneic hematopoietic cell transplantation in children and adults: a study from the Infectious Diseases Working Party of the European Society for Blood and Marrow Transplantation - Styczynski, Jan; Tridello, Gloria; Knelange, Nina; Wendel, Lotus; Ljungman, Per; Mikulska, Malgorzata; Gil, Lidia; Cesaro, Simone; Averbuch, Diana; von dem Borne, Peter; Xhaard, Aliénor; Mielke, Stephan; et al. (Bone Marrow Transplantation, 2024)
The objective of the study was the analysis of clinical types, outcomes, and risk factors associated with the outcome of adenovirus (ADV) infection, in children and adults after allo-HCT. A total number of 2529 patients (43.9% children; 56.1% adults) transplanted between 2000 and 2022 reported to the EBMT database with diagnosis of ADV infection were analyzed. ADV infection manifested mainly as viremia (62.6%) or gastrointestinal infection (17.9%). The risk of 1-year mortality was higher in adults (p = 0.0001), and in patients with ADV infection developing before day +100 (p < 0.0001). The 100-day overall survival after diagnosis of ADV infections was 79.2% in children and 71.9% in adults (p < 0.0001). Factors contributing to increased risk of death by day +100 in multivariate analysis, in children: CMV seropositivity of donor and/or recipient (p = 0.02), and Lansky/Karnofsky score <90 (p < 0.0001), while in adults: type of ADV infection (viremia or pneumonia vs gastrointestinal infection) (p = 0.0004), second or higher HCT (p = 0.0003), and shorter time from allo-HCT to ADV infection (p = 0.003). In conclusion, we have shown that in patients infected with ADV, short-term survival is better in children than adults. Factors directly related to ADV infection (time, clinical type) contribute to mortality in adults, while pre-transplant factors (CMV serostatus, Lansky/Karnofsky score) contribute to mortality in children.
Publisher: Nature Publishing Group
Keywords: Risk factors; Stem-cell research